Comparative Analysis of Ideational Metafunction between Presenters in Talk Show - Fulki Syarafina Aldisan; Hamzah Hamzah (English Language and Literature, 2022)
This study aims to examine the similarities and differences of meaning in language style used ideational metafunction in Kick Andy and Mata Najwa talk show. The purpose of this research is to find similarities and differences of in meaning language style used ideational metafunction of Matthiessen (2014). The object of this research are Kick Andy and Mata Najwa talk show videos from Youtube channel. The method of this research uses descriptive qualitative research. The result of this research show two similarities and four differences in level ideational metafunction. The conclusion of this study there are more differences rather then similarities, because the differences in style are affected by different gender which are presented through lead and speech to the different ways of selection and producing of word in the ideational of metafunction.